Small and medium enterprises and access to finance in Egypt - Houssien, Ismail (AUC Knowledge Fountain, 2014)
The purpose of this study is to put a spotlight on some of the problems of access to finance that stand in the way of small and midsize enterprises (SMEs) in Egypt and to draw the attention of policy makers to try to solve those issues. These problems vary from financial issues such as getting access to money to non-financial shortcomings in such areas as knowhow, marketing, management and accounting systems. Furthermore, SMEs in Egypt suffer from complex governmental regulations as well. To address the overall research question, Ã¢â‚¬Å“how do informal areas SMEs meet their financing needs and why do they make these choices,Ã¢â‚¬Â the study used interviews and a written questionnaire both conducted with SME owners in the informal area of Imbaba in Giza. The study found that a large majority of SMEs have never used formal financial institutions due to lack of knowledge about how to deal with banks and the banksÃ¢â‚¬â„¢ complicated procedures. A minority of those surveyed did use bank loans but suffered great difficulty in dealing with the system, repaying the loan, and dealing with high interest rates. The field work was complemented by a review of the literature, which found that banks' regulations and minimum loan size discourages SME owners from trying to obtain bank finance. Many interviewees expressed their anger at the complex and seemingly purposeless documentation required to obtain loans. Cut off from formal funding, most of the workshop owners interviewed depends on their social ties for financing, borrowing money from relatives and friends or participating in rotating credit associations. The study recommends that greater efforts be made by the government to ease regulations on starting a business. Banks should more aggressively pursue SME business, visiting shops and working with the owners to remove barriers to credit. NGOs should give assistance to shops facing difficulties in repayment to address the causes of their problems. If greater efforts are not made by the government and others to improve access to finance, SMEs will not be able to grow as quickly, with negative impacts on the Egyptian economy and on societal problems such as unemployment.